Efektivitas Pemanfaatan Lembar Kerja Siswa (LKS) dalam peningkatan kualitas Pembelajaran Pendidikan Agama Islam (PAI) di SMP Negeri 4 Watampone - Febri Anto Nur, Alim (Institut Agama Islam Negeri (IAIN) Bone, 2020)
This article examines the implementation of Student worksheet utilization (LKS) in improving the quality of Islamic religious education (PAI) in State SMP 4 Watampone, this research is a field research. The presentation of data is done in a qualitative descriptive, which is a research that can be seen from the experts is data descriptively (depiction) that is the oral facts and the writing of each person's behavior is reflected. The results showed that LKS was a teaching material that remained in place in accordance with the existing curriculum for class VII and VIII using curriculum 2013 and for class IX using KTSP kurukulum. The presence of LKS in the learning process is very easy for teachers to convey material as well as giving assignments. Students also feel happy when teachers use different methods of using LKS in teaching activities in classrooms. Generally the tasks that teachers provide using individual and group patterns, learning goals are expected to create an atmosphere that is active, innovative, creative, effective and enjoyable. The contribution of Student Worksheets (LKS) is seen from the students ' learning outcomes that have increased by using LKS. Then the process of interacting in the classroom between teachers and students, the interaction of students and teachers is properly realized. In addition, the material that resides in the LKS PAI can be subject to life-day.